2015
DOI: 10.1097/01.epx.0000470563.41655.71
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment against nursing staff in Tanta University Hospitals, Egypt

Abstract: The prevalence of sexual harassment among nurses at the workplace was high with relation to certain occupational factors, and it led to marked psychological effects on the victims. Hence, protective legislations and measures should be taken by the hospital management for prevention of this problem in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 17 publications
4
23
1
Order By: Relevance
“…The 6-month prevalence was 13.0% in one study in Ethiopia (Fute et al, 2015), while the prevalence in the past 2 years was 45.0% in one study in Australia (Cogin & Fish, 2009). Seven studies reported the prevalence of sexual harassment without timeframes: the prevalence were 71.5% in Pakistan (Mushtaq et al, 2015), 70.2% in Egypt (Ali et al, 2015), 56.0% in Japan (Hibino, Hitomi, Kambayashi, & Nakamura, 2009), 37.1% in Turkey (Celik & Celik, 2007), 9.4% in Saudi Arabia (Mohamed, 2002), 65.8% in the USA (West, Holoviak, & Figler, 1995), and 71.8% in the USA (Libbus & Bowman, 1994).…”
Section: Prevalence Of Sexual Harassmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The 6-month prevalence was 13.0% in one study in Ethiopia (Fute et al, 2015), while the prevalence in the past 2 years was 45.0% in one study in Australia (Cogin & Fish, 2009). Seven studies reported the prevalence of sexual harassment without timeframes: the prevalence were 71.5% in Pakistan (Mushtaq et al, 2015), 70.2% in Egypt (Ali et al, 2015), 56.0% in Japan (Hibino, Hitomi, Kambayashi, & Nakamura, 2009), 37.1% in Turkey (Celik & Celik, 2007), 9.4% in Saudi Arabia (Mohamed, 2002), 65.8% in the USA (West, Holoviak, & Figler, 1995), and 71.8% in the USA (Libbus & Bowman, 1994).…”
Section: Prevalence Of Sexual Harassmentmentioning
confidence: 99%
“…This is partly attributed to the discrepancies in assessment tools, sample size, sampling methods, and relevant policies and legislation. Sexual harassment towards nurses has deleterious effects, such as high stress, poor mental health and quality of life, burnout, job dissatisfaction, and poor work quality and efficiency (Ali, Saied, Elsabagh, & Zayed, 2015;Charney & Russell, 1994;Kisa, Dziegielewski, & Ates, 2002;Mushtaq, Sultana, & Imtiaz, 2015;Nielsen et al, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…When attending a patient, nursing staff are often in close or even physical contact with the patient; for example, checking vital signs, assisting in changing positions, changing wound dressings, etc., which increases the possibility of being harassed. Studies have shown that the proportion of patients or family members harassing registered nurses is 18–69.1% [ 5 , 6 , 7 ]. Therefore, nurses are considered to be at a high risk of workplace sexual harassment [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the proportion of patients or family members harassing registered nurses is 18–69.1% [ 5 , 6 , 7 ]. Therefore, nurses are considered to be at a high risk of workplace sexual harassment [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%